سياسة الاستيطان الإسباني في البيرو في القرن السادس عشر (Journal of the College of Basic Education, 2022)
The policy of the Spanish government towards the New World was not limited to the idea of ​​trade exchange and the establishment of commercial stations in the discovered areas, but the settlement in those lands in order to transform them into the Catholic faith and the European civilization with all its features. Thus, the lands of the New World became not an area for scouting adventures, but rather areas for the settlement of many of The Spaniards, and in the first half of the sixteenth century, the Spaniards succeeded in conquering Mexico and Peru, laying the foundation stone for a Spanish empire in the New World, thus supporting the growth of the world market because those possessions provided them with much-needed money for political and economic expansion through their acquisition of precious metals (gold and silver ) in the New World, which had a severe impact on European prosperity.The research discusses the beginning of the Spanish settlement in Peru, then sheds light on the policy of organizing and expanding the settlement administration in Peru for the period 1518-1598, reviewing the most important laws that were enacted as a new stage in the Spanish administrative structure in the New World.